2022
DOI: 10.1155/2022/4392256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aronia Extract on Collagen Synthesis in Human Skin Cell and Dermal Equivalent

Abstract: The regulation of collagen synthesis, which occurs in fibroblasts in the dermal layer, is a key process in dermis regeneration and skin reconstruction. Herein, we investigated whether Aronia melanocarpa extract affects the human skin condition. We focused on type I collagen synthesis using two different types of model systems: a monolayer of cells and a bioprinted 3D dermal equivalent. The Aronia extract showed no cytotoxicity and increased cell proliferation in neonatal human dermal fibroblasts. Treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Their research, facilitated by the development of 3D skin models, revealed that the Aronia extract enhanced the synthesis of type I collagen and reduced the expression of MMP1 and MMP3. These findings suggest that this extract could be beneficial in treating damaged or aged skin [81].…”
Section: Inkjet-printed Tissues and Organsmentioning
confidence: 71%
“…Their research, facilitated by the development of 3D skin models, revealed that the Aronia extract enhanced the synthesis of type I collagen and reduced the expression of MMP1 and MMP3. These findings suggest that this extract could be beneficial in treating damaged or aged skin [81].…”
Section: Inkjet-printed Tissues and Organsmentioning
confidence: 71%
“…Маски из данного богатого витамином C и прочими полезными микроэлементами продукта способствуют ускоренному синтезу коллагена в тканях и рекомендуются специалистами для безопасного и эффективного лечения стареющей и поврежденной дермы. [24] 10. Полезен для спортсменов-бегунов Бег на длинные дистанции может быть опасен для бегунов-любителей -повышенные кардионагрузки увеличивают риски остановки сердца за счет усиления активации тромбоцитов.…”
Section: улучшает состояние кожных покрововunclassified
“…Additionally, it has been shown that the consumption of chokeberry juice may have hypotensive, lipid-lowering, and hypoglycemic effects, as well as reduce the levels of liver enzymes [ 18 , 19 , 20 ]. Studies on animals or cell cultures report chokeberry’s hepatoprotective [ 21 , 22 ], anti-inflammatory [ 23 , 24 , 25 ], neuroprotective [ 26 , 27 ], antidepressant [ 28 ], anti-aging [ 29 ], anticancer [ 30 ], antiviral [ 31 ], and antibacterial effects [ 32 ]. Because of their contents of valuable health-promoting ingredients, chokeberry products can be used both in the prevention and support of the treatment for existing metabolic disorders [ 18 ].…”
Section: Introductionmentioning
confidence: 99%